THE LEADERSHIP ROLE FOR A SUCCESSFUL CHANGE MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Magnasofa, Meike; Najib, Mardiati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Globally there are significant concerns about the role of leadership in the disruptive era where change is inevitable. Organization needs a leader who can response those changes toward right direction to sustain. This review is to identify a more comprehensive relation between the leadership role and change management in the organization and its associated factors drawing upon systematic review of literatures published in the last ten years. Methods: This study used systematic literature review based on the PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses) protocol to identify all the published articles using relevant keywords. We searched in Emerald Insight (2010-2019), Science Direct (2010-2019), and EBSCOhost (2010-2019) to retrieve relevant articles published in English language only between January 2010 and April 2019. The review used key terms and phrases associated with Leadership, Change Management, and Disruptive. The abstracts were reviewed according to inclusion criteria and quality assessment. Results: From 16,658 authors finally include 6 papers in this review. By the review, we noted that it is almost impossible to avoid change although resistance to change is real. There is a positive relation between leadership role and successful change management. The most significant subject and contributor for the successful change are the culture of change within the organization and the effective communication between leaders and their subordinates. The hindrances of change are lack of authority, uncertainly of role and lack of time and focus from the leaders. The findings of the study can be relevant for variety of settings as the study was conducted across cultures and sectors. Conclusions: Leaders need to understand and spread the ambience with their employee of 4 points; the clarity about the needs of change in their organization, the key alignments, complementary development strategies and critical enablement. The recommendation for future research is to review more leadership studies on disruptive era in health care sector only in order to get deeper understanding in homogeneity setting. For policy makers, it is suggested to design policy that enforces leaders to improve their leadership skill and updating knowledge.